Effect of ball-burnishing on hydrogen-assisted cracking of a martensitic stainless steel. (1st December 2022) - Dreano, A.; Alnajjar, M.; Salvatore, F.; Rech, J.; Bosch, C.; Wolski, K.; Kermouche, G.; Christien, F.
Abstract: Slow strain rate tensile tests under hydrogen cathodic charging are conducted on 17-4 PH steel with two surface conditions: mirror polished and ball-burnished. In both cases, significant subcritical cracking initiating at the surface is observed leading to considerable reduction in elongation to fracture. However, ball-burnished specimens show better elongation and much less secondary cracking than the polished ones. Ball-burnishing introduces high compressive residual stresses in the specimen sub-surface. However, EBSD showed a very limited impact of ball-burnishing on the microstructure, so little effect on hydrogen trapping is expected. The beneficial effect of ball-burnishing on the resistance of the hydrogen assisted cracking is mainly explained by the high compressive longitudinal stress at the specimen surface, which makes crack initiation more difficult and hence delays specimen failure. In addition, it is estimated that the amount of hydrogen introduced at the specimen surface is decreased by approximately 30% due to the high compressive hydrostatic stress. Graphical abstract: Image 1 Highlights: Ball-burnished specimens are mechanically tested in hydrogen-rich environment. Ball-burnishing results in high compressive residual stress and limited roughness. A better resistance to HE is observed when specimens are ball-burnished. The introduction of CRS at the surface delays the specimen failure.